MENGENAL RIDA K LIAMSI SEBAGAI TOKOH SASTRAWAN MELAYU RIAU - Herlia, Ela; ', Prof. Dr. Isjoni, M.Si; ', Asril, M.Pd (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Rida K Liamsi is a literary and cultural figures intellect and preservation of the malay culture. This proved Rida K Liamsi pleased with his attention to the preservation and development ofmalay culture, its physical evidence Rida K Liamsi make sanganng foundations, many of his writings in the from of poems, essays, articles, novels, and books themed Malay culture. One book of poems Rida K Liamsi is “TEMPULING”. For the people of Riau Rida K Liamsi name is well known, in the world of traditional Malay and Malay literature. As for the purpose of this study is To know the life history characters Rida K Liamsi, To find out how the role and efforts Rida K Liamsi in developing Riau Malay literature and culture, To know the constraints faced Rida K Liamsi in developing Riau Malay literature and culture, To find work Rida K Liamsi in Riau Malay literature, To know the grace of awards and titles which have been obtained traitor Rida K Liamsi as Riau Malay literary figures. The method used in this study is the historical method and qualitative metide. Date were obtained from interviews later in the analysis itself. As for its research sites in the city of Pekanbaru Riau. When research started from the seminar proposal to the thesis examination. Date collection techniques used were observasion, interview, techniques, technical documention, and literature. Of the research say that the Rida K Liamsi is a figure literary and culture malay Riau whose role is to develop and preserve literatureand culture through the work, established a foundation Sagang, held KAPLF II Riau, gives grace sagang to young people who work, as well as being pioner days of Indonesia. Rida K Liamsi works like a collection of poetry Ode X (1981), Tempuling (2002), Perjalanan Kelakatu (2008), dan Rose (2013), Ombak Sekanak (2013), malay novel with a background story of the 19 century, Bulang Cahaya (2007). Degrees and awards in Rida K Liamsi get not only at a National level has even reacthe international level. Jaunty series of cultural progenitor degree, degree prime artists, boon as the driving socio, cultural figures, a boon as the driving character of traditional arts and cultural figures.Key Words: Riau, Malay, Writers2